Pembelajaran Bahasa Arab di MI NU Tratee Putera Gresik - Salsabila, Luthfiya (Maliki Interdisciplinary Journal, 2023)
In the process of teaching Arabic language, teachers have generally provided examples of simple texts taken from textbooks, but often lacked variety in the utilization of teaching methods. As a result, students' interest in learning the Arabic language has diminished. However, at MI NU Tratee Putera Gresik, the applied teaching method has successfully overcome this monotony and ignited students' enthusiasm for learning Arabic. Through this article, the author will elaborate on how the adopted Arabic language teaching method at MI NU Tratee Putera Gresik can deliver a more engaging and effective learning experience.